Novelties in Macrofungi of the Tropical Montane Cloud Forest in Mexico - Ricardo Valenzuela; Isolda Luna-Vega; Michelle Martínez-Pineda; César Ramiro Martínez-González; Jesús García-Jiménez; Javier de la Fuente; Silvia Bautista-Hernández; Salvador Acosta-Castellanos; Tania Raymundo (Journal of Fungi, 2023)
The tropical montane cloud forest in Mexico is the most diverse and threatened ecosystem. Mexican macrofungi numbers more than 1408 species. This study described four new species of Agaricomycetes (Bondarzewia, Gymnopilus, Serpula, Sparassis) based on molecular and morphological characteristics. Our results support that Mexico is among the most biodiverse countries in terms of macrofungi in the Neotropics.